Moderasi Beragama pada Portal Keislaman: Analisis Islami.co Perspektif Relasi Kuasa Michel Foucault - Achmad Tohari; Neneng Mujlipah (Universitas Islam Negeri Madura, 2024)
This paper discusses the phenomenon that exists in many digital media that use religion as a tool to boost the position of the press, many portals or even media display da'wah segments that many people easily understand, but some media are only used for propaganda of mere interests. The method used in this research is qualitative combined with literature review research on sources and journals that are still relevant to the research. This research explains about Islamic portals in their narratives that have experienced significant development, especially Islamist media whose impression dominates digital space in Indonesia, the data used in this case uses Michel Foucault's power relations theory as a media discourse analysis knife. The findings in the study are that the knowledge built by islami.co media is more about disseminating discourse or in power theory, namely disciplinary power, something that shows that there is a power relationship between helping, instilling, and controlling the body, so it can be understood that islami.co has the authority for knowledge aimed at understanding religious moderation on Islamic portals.